QUANTITATIVE ANALYSIS AND LIGNIN HISTOCHEMICAL ASSAY OF SENGON (Paraserianthes falcataria) - N. Sri Hartati; Enny Sudarmonowati; Suharso Suharso; Kurnia Sofyan (Pusbindiklat - LIPI, 2011)
The presence of lignin in plant cells is a factor limiting the effi ciency of processing lignocellulosic materials of wood-based industries including pulp and paper industry either chemically or biologically (biopulping) process using white rot fungi. Lignin content determination of sengon collected from different areas in Indonesia indicated that it ranged low to moderate category (16.58–35.59%). Lignin histochemical assay of transverse section of stems using phloroglucinol-HCl staining showed that the initiation of lignin deposition was noted in 2 weeks old seedling. Lignin quantitative and qualitative assessment through histochemical assay showed that lignin content was varied in trees depending on height